DIFFERENT LEARNING STYLES AND THEIR IMPLICATIONS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article is about learning styles and their importance. How they can impact on learners or to the process of teaching. as each individual hasdifferent rules for learning… Driven own interpretation of new experiences and knowledge from an early age. How much any individual learns is very much related to whether educational experience is geared towards their particular learning style